Suture Superior to Staples for Skin Closure after Cesarean Section - Nierengarten, Mary Beth (MD Conference Express, 2014)
Use of suture to close the skin after a cesarean section is associated with superior overall satisfaction, as well as superior cosmetic satisfaction and outcomes, compared with the use of staples. This is the conclusion of a study to compare patient satisfaction and cosmetic outcomes between 2 of the most common methods of skin closure after cesarean section.